The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1177/0031512520983680
|View full text |Cite
|
Sign up to set email alerts
|

Wellness Survey Responses and Smartphone App Response Efficiency: Associations With Remote History of Sport-Related Concussion

Abstract: Recent research findings have strongly suggested that sport-related concussion (SRC) increases risk for subsequent injury of any type, as well as a potential for long-term adverse effects on neurological and psychological well-being. The primary purpose of this study was to explore the reliability and discriminatory power of clinical testing procedures for detecting persisting effects of SRC. We used a cross-sectional study design to assess both self-reported symptoms commonly associated with post-concussion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…The Institutional Review Board of the University of Tennessee at Chattanooga approved all study procedures. Surveys administered prior to initiation of the first training session included the Sports Fitness Index (Wilkerson et al, 2016), the Overall Wellness Index (Wilkerson et al, 2021b), and the Depression, Anxiety, and Stress Scale (Edmed and Sullivan, 2012), which were used to confirm greater frequency of selfreported problems among the athletes who affirmed a history of at least one SRC (HxSRC).…”
Section: Methodsmentioning
confidence: 99%
“…The Institutional Review Board of the University of Tennessee at Chattanooga approved all study procedures. Surveys administered prior to initiation of the first training session included the Sports Fitness Index (Wilkerson et al, 2016), the Overall Wellness Index (Wilkerson et al, 2021b), and the Depression, Anxiety, and Stress Scale (Edmed and Sullivan, 2012), which were used to confirm greater frequency of selfreported problems among the athletes who affirmed a history of at least one SRC (HxSRC).…”
Section: Methodsmentioning
confidence: 99%
“…The surveys included a Sport Fitness Index (SFI), which documents self-ratings of persisting effects of prior musculoskeletal injuries, 55 and an Overall Wellness Index (OWI), which is designed to document the temporal proximity and the frequency of physical, cognitive, behavioral, sleep-related, and mood disorders associated with postconcussion syndrome ( Appendix Figure A1 ). 54 Responses to 10 items on both the SFI and the OWI were used to generate 0 to 100 scores for each, with low values indicating suboptimal status. Previous research has demonstrated good internal consistency for both the SFI score 55 (Cronbach α = .89) and the OWI score 54 (Cronbach α = .82).…”
Section: Methodsmentioning
confidence: 99%
“… 54 Responses to 10 items on both the SFI and the OWI were used to generate 0 to 100 scores for each, with low values indicating suboptimal status. Previous research has demonstrated good internal consistency for both the SFI score 55 (Cronbach α = .89) and the OWI score 54 (Cronbach α = .82). The OWI does not make any reference to concussion, but its 10 categories of problems include 82 postconcussion symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smartphones have a repertoire of mobile tools, which altered the consumption dynamics and the way users interact [7]. In particular, consumer and information applications as well as social networks have high demand, and have high in uence in individual communication and lifestyle habits [8].…”
Section: Introductionmentioning
confidence: 99%